Surfing paddling and swimming kinematics comparison - Godoy, D. F.; Correia, R. de A.; Feitosa, W. G.; Franken, M.; de Souza Castro, F. A. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Surfers who live far from the ocean use to swim in pools as a training content. Considering the similarities between the front crawl stroke and surfing paddling movements, the objective of this study was to compare surfing paddling and front crawl kinematics parameters. In a 25-m swimming pool, fourteen recreational surfers (37.7 ± 4.7 years old; 21.2 ± 6.7 years of experience in surfing; 77.7 ± 7.7 kg total body mass) performed two tests in same duration and both in maximum intensity: (i) a 300-m front crawl test and (ii) a paddling test with soft board. Mean values of stroke rate (SR), stroke length (SL) and speed (S) were obtained in 2D with video cameras (60 Hz, videos analyzed in Kinovea®). Hull-speed (HS) and hull-speed related to S (HS%) were calculated considering both, stature (for swimming condition) and surfboard length (for paddling condition). Data were compared with Student`s t test and effects sizes were calculated with Pearson`s r. In the same test duration (322.0 ± 33 s), surfers have paddled for 415.2 ± 36.6 m (300 m in front crawl swimming). Paddling showed higher SR, S, HS, and HS% values (p<0.05) when compared to swimming (respectively, paddling: 0.94 ± 0.09 Hz; 1.27 ± 0.1 m/s; 1.71 ± 0.05 m/s; 74.70 ± 6.55%; and swimming: 0.57 ± 0.07 Hz, 0.91 ± 0.14 m/s, 1.67 ± 0, 03 m/s; 55.01 ± 9.2%). One should consider the mean length of the surfboard (193 ± 14.1 cm) and the mean height of the surfers (177.8 ± 7.1 cm) to compare the HS and the HS% values between the conditions. Effects size were between 0.43 and 0.72. SL values were similar (p>0.05; paddling: 1.73 ± 0.23 m; swimming: 1.58 ± 0.21 m; effect size=0.32). It is concluded that efforts and tests (front crawl and paddling) are not interchangeable for kinematics parameters.